1994
DOI: 10.1161/01.cir.90.4.1832
|View full text |Cite
|
Sign up to set email alerts
|

Rate-dependent properties of adenosine-induced negative dromotropism in humans.

Abstract: BACKGROUND The antiarrhythmic effects of sodium channel and calcium channel blockers are known to be rate dependent. Little is known about the rate-dependent effect of adenosine on human atrioventricular (AV) nodal conduction. The purpose of this study was to determine whether the negative dromotropic effect of adenosine is dependent on heart rate. METHODS AND RESULTS Atrial pacing at 20-millisecond increments decreasing stepwise was performed, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
0
12
1
Order By: Relevance
“…It has been shown that the negative dromotropic effect of adenosine tends to increase when the atrial pacing cycle is progressively reduced during experimental PSVT, 17 and the rate-dependent conduction slowing seems to be more pronounced for adenosine than for verapamil. 19 Adenosine has been demonstrated to increase AV-nodal fatigue -i.e., the AV-nodal delay which slowly develops at fast rates -and to attenuate facilitation -i.e., the tendency of short cycles to improve subsequent nodal recovery -without directly altering AV-nodal recovery, and this may result in frequencydependent increases in the AV-nodal conduction time and effective refractory period.…”
Section: Probability Of Success (%)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the negative dromotropic effect of adenosine tends to increase when the atrial pacing cycle is progressively reduced during experimental PSVT, 17 and the rate-dependent conduction slowing seems to be more pronounced for adenosine than for verapamil. 19 Adenosine has been demonstrated to increase AV-nodal fatigue -i.e., the AV-nodal delay which slowly develops at fast rates -and to attenuate facilitation -i.e., the tendency of short cycles to improve subsequent nodal recovery -without directly altering AV-nodal recovery, and this may result in frequencydependent increases in the AV-nodal conduction time and effective refractory period.…”
Section: Probability Of Success (%)mentioning
confidence: 99%
“…6;7 When no haemodynamic instability is present, vagal manoeuvres, adenosine and verapamil are usually considered as the first-line treatment of choice for PSVT, [8][9][10] and the relative efficacy of each has been evaluated in many studies. [11][12][13][14][15][16] Both adenosine and verapamil are well known to have a frequency-dependent effect on functional AV-nodal properties, [17][18][19] and the rate-dependence of depression in AV-nodal function has been reported to play a key role in the ability of interrupting experimental pacing-induced PSVT. 20 These findings suggest that the rate of the tachycardia may potentially affect the anti-arrhythmic efficacy of both drugs in spontaneous PSVT.…”
Section: Introductionmentioning
confidence: 99%
“…None of the patients had received any drug that was known to interfere with the effects of adenosine (e.g., theophylline, dipyridamole). Using conventional methods [14,15], three quadripolar and one decapolar electrode catheters were introduced into the right femoral vein and advanced to high right atrium, right AV junction, right ventricular apex, and coronary sinus, respectively, for recording and stimulation. Bipolar intracardiac electrograms filtered between 30 and 500 Hz simultaneously with 12-lead surface electrocardiograms were recorded and stored digitally on a recording system (Bard).…”
Section: Electrophysiological Studymentioning
confidence: 99%
“…In considering the use-dependent effect of adenosine on AV nodal conduction [15], we compared the effects of adenosine on antegrade SP conduction (during AVNRT) and retrograde FP conduction (during constant right ventricular pacing) at the identical cycle length and showed that the effect of adenosine was more potent on the antegrade SP conduction than on the retrograde FP conduction. The response of antegrade FP to adenosine could be measured under the following two conditions: (1) before catheter ablation of the SP, during constant high right atrial pacing with 1:1 conduction through antegrade FP, when adenosine induced a sudden marked prolongation of the AH interval (usually 150 ms), the impulse was considered as blocking at the antegrade FP and conducting through the antegrade SP, and (2) after completely selective catheter ablation of the antegrade SP conduction, the residual 1:1 AV conduction is exclusively through the antegrade FP, therefore, the dose-response curve of antegrade FP to adenosine could be obtained.…”
Section: Comparing the Effects Of Adenosine On The Three Av Nodal Patmentioning
confidence: 99%
“…The A-V-nodal effects of adenosine are related to the opening of G ibg -coupled K 1 channels as well as to a depression of I Ca,L (Wang et al, 1996). As a result, adenosine causes rate-dependent impairment of A-V-nodal function that results in substantial and effective block at rapid rates (Nayebpour et al, 1993;Lai et al, 1994). Nevertheless, the therapeutic utility of adenosine is limited to the acute treatment of A-V-nodal-dependent Paroxysmal supraventricular tachycardia owing to its extremely short physiological half-life and its hemodynamic side effects, which are mainly related to the activation of A 2A receptors (Wilbur and Marchlinski, 1997).…”
Section: Introductionmentioning
confidence: 99%